Childhood and adult company: New intergenerational transmission of culture and new learning strategy - Nenadić Mile N. (Visoka škola strukovnih studija za vaspitače, Kruševac, 2014)
The paper promotes the idea that childhood is relevant and significant both as a social institution and as a social and cultural construct. The author holds the view that mainstream society comprises children as well as adults, and that consequently children should be given priority over the rest of the human race, and childhood should be given priority within society. In order to emphasize the need for recognition of childhood, the author in several ways brings attention to the problem of children's identity and draws distinction between it and adult identity. Special emphasis is placed on the problem of childhood and school system. School systems recognize only their own, school culture, but not children's culture. Recognition of childhood would bring about a profound change - just the type of change so badly needed by postmodern education. The deepest change would concern the change in intergenerational transmission of culture. Without new intergenerational transmission of culture all other linking strategies would remain simply technical projections of the possible 'disappearance of childhood'. Electronic media, especially the internet, level out the difference between the adult world and the children's world, so much so that it seems that children develop far more quickly intellectually than morally and psychically. The fact that school distances itself from children's culture results in misrecognition of childhood and creates a limiting, humiliating and disparaging image of it. School that would correct this is sorely needed.